2017
DOI: 10.1038/s41594-017-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Postmitotic nuclear pore assembly proceeds by radial dilation of small membrane openings

Abstract: The nuclear envelope has to be reformed after mitosis to create viable daughter cells with closed nuclei. How membrane sealing of DNA and assembly of nuclear pore complexes (NPCs) are achieved and coordinated is poorly understood. Here, we reconstructed nuclear membrane topology and the structures of assembling NPCs in a correlative 3D EM time course of dividing human cells. Our quantitative ultrastructural analysis shows that nuclear membranes form from highly fenestrated ER sheets whose holes progressively s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 37 publications
11
104
0
Order By: Relevance
“…In this study, we showed a third model, in which fenestrations or empty holes present in the sheet‐like ER membranes are used to assemble the NPC during telophase (Figures and Supporting Information Figure S2). Our findings are consistent with those of other groups (Otsuka et al, ). Formation of fenestrations on the sheet‐like membrane is regulated by combination of types of curvature‐stabilizing proteins: reticulon family proteins, DP1/Yop1 family proteins and lunapark protein (Shemesh et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we showed a third model, in which fenestrations or empty holes present in the sheet‐like ER membranes are used to assemble the NPC during telophase (Figures and Supporting Information Figure S2). Our findings are consistent with those of other groups (Otsuka et al, ). Formation of fenestrations on the sheet‐like membrane is regulated by combination of types of curvature‐stabilizing proteins: reticulon family proteins, DP1/Yop1 family proteins and lunapark protein (Shemesh et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…The order in which Nups assemble during postmitotic assembly has been studied in Xenopus egg extract and fixed human cells at different cell-cycle stages [88][89][90][91][92]. Additional structural insight comes from in vivo studies of rat and human cell lines [93][94][95][96]. Postmitotic assembly of NPCs happens in organisms with open mitosis upon mitotic exit, in telophase.…”
Section: Two Mechanisms Of Npc Assembly: Postmitotic Assemblymentioning
confidence: 99%
“…These architectural units are themselves constructed from modular subcomplexes of proteins termed nucleoporins or nups that are assembled step-wise into the NE, with an emerging role for unstructured motifs that connect subcomplexes together to help build the NPC[810]. There remains considerable interest in understanding the biochemical and morphological differences that define post-mitotic and interphase modes of NPC assembly[1113]. Of note, recent evidence supports that post-mitotic NPC assembly begins within small (<50 nm) pores in the reforming NE, whereas interphase NPC assembly requires an INM-ONM fusion event[12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There remains considerable interest in understanding the biochemical and morphological differences that define post-mitotic and interphase modes of NPC assembly[1113]. Of note, recent evidence supports that post-mitotic NPC assembly begins within small (<50 nm) pores in the reforming NE, whereas interphase NPC assembly requires an INM-ONM fusion event[12,13]. Interestingly, the molecular fusogen that drives INM-ONM fusion has eluded genetic (or biochemical) identification.…”
Section: Introductionmentioning
confidence: 99%